2021
DOI: 10.1002/isaf.1503
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Drivers and Barriers of Artificial Intelligence Adoption: Insights from a Strategic Management Perspective

Abstract: Summary Artificial intelligence (AI) in business processes and academic research in AI has significantly increased. However, the adoption of AI in organizational strategy is yet to be explored in extant literature. This study proposes two conceptual frameworks showing hierarchical relationships among the various drivers and barriers to AI adoption in organizational strategy. In a two‐step approach, the literature study is first done to identify eight drivers of and nine barriers to AI adoption and validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…One study, amongst others, has recognized several barriers and their associations with each other, each negatively impacting the enterprise-wide scaling of AI [42]. It suggests that challenges, such as a lack of reusable models, reside on the first level, followed by a lack of usable data and trust in AI on the second level.…”
Section: Barriers To Ai Usagementioning
confidence: 99%
See 2 more Smart Citations
“…One study, amongst others, has recognized several barriers and their associations with each other, each negatively impacting the enterprise-wide scaling of AI [42]. It suggests that challenges, such as a lack of reusable models, reside on the first level, followed by a lack of usable data and trust in AI on the second level.…”
Section: Barriers To Ai Usagementioning
confidence: 99%
“…It suggests that challenges, such as a lack of reusable models, reside on the first level, followed by a lack of usable data and trust in AI on the second level. The threat of job security, poor infrastructure for AI model deployment, and a paucity of the AI talent and skills required are some other barriers to AI scalability [42]. In a quantitative study [43], the main obstacle is identified as a lack of adequate AI skills and talent to deploy AI models successfully [43].…”
Section: Barriers To Ai Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning should be regarded as a powerful addition to the existing body of ML models instead of a "one size fits all " solution. Earlier studies ( Chui et al, 2018 ;Grover, Kar, & Dwivedi, 2022 ;Kar et al, 2021 ;Samek & Müller, 2019 ) have identified different barriers to AI adoption as computational complexity, missing big data infrastructure, lacking transparency, skill shortage, leadership commitment, and missing strategic guidance. All of those findings have the potential to impact the adoption speed of DL across different domains.…”
Section: Contributions To Literaturementioning
confidence: 99%
“…(4) Skill Shortage: Talent ( Kar, Kar, & Gupta, 2021 ) is required to implement those models as well as subject matter expertise to define use cases ( Henke et al, 2016 ). The current supply and demand gap for ML experts makes it difficult for small-and medium-sized corporations to utilize advanced AI.…”
Section: Introductionmentioning
confidence: 99%